1993
DOI: 10.1159/000292666
|View full text |Cite
|
Sign up to set email alerts
|

A Follicular Cyst during Tamoxifen Therapy in a Premenopausal Breast Cancer Woman

Abstract: A large ovarian follicular cyst developed on day 43 of low-dose tamoxifen adjuvant therapy for a premenopausal breast cancer (total drug intake: 860 mg). The serum estradiol level increased to almost ten times the pretreatment level. However, the FSH and LH decreased slightly, and the serum progesterone level remained almost unchanged. It is hypothesized that tamoxifen acted directly on the ovaries to provoke excessive proliferation of the granu-losa cells in a follicular cyst, causing it to grow very large, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Over the last decade concern about the side-effects of tamoxifen has focused mainly on the occurrence of endometrial carcinoma with a 2.3-6.4-fold increased risk compared to non-using patients (Fornander et al, 1989;Andersson et al, 1991;Van Leeuwen et al, 1994). Ovarian cyst formation during tamoxifen has been reported in single cases (Jolles et al, 1990;Barbieri et al, 1993;Seoud et al, 1993;Terada et al, 1993;Cohen et al, 1994;Shulman et al, 1994;Re et al, 1994), in a breast cancer prevention study (Powles et al, 1994) and in series of tamoxifen-treated breast cancer patients (Boccardo et al, 1992;Cohen et al, 1996;Shushan et al, 1996). However, it is unclear which patients are prone to develop ovarian cysts and if the presence of cysts is of any clinical relevance.…”
mentioning
confidence: 99%
“…Over the last decade concern about the side-effects of tamoxifen has focused mainly on the occurrence of endometrial carcinoma with a 2.3-6.4-fold increased risk compared to non-using patients (Fornander et al, 1989;Andersson et al, 1991;Van Leeuwen et al, 1994). Ovarian cyst formation during tamoxifen has been reported in single cases (Jolles et al, 1990;Barbieri et al, 1993;Seoud et al, 1993;Terada et al, 1993;Cohen et al, 1994;Shulman et al, 1994;Re et al, 1994), in a breast cancer prevention study (Powles et al, 1994) and in series of tamoxifen-treated breast cancer patients (Boccardo et al, 1992;Cohen et al, 1996;Shushan et al, 1996). However, it is unclear which patients are prone to develop ovarian cysts and if the presence of cysts is of any clinical relevance.…”
mentioning
confidence: 99%
“…Nonetheless, the mechanism by which tamoxifen leads to ovarian cyst formation which has been widely discussed (14), (15), (34) and (35) is likely to be the underlying mechanism in this case too. Jolles et al (1990) have proposed that tamoxifen being a SERM may have a similar mode of action to clomephine on the hypothalamus leading to increased endogenous gonadotrophin release from the pituitary gland causing either cystic enlargement of the ovary or proper OHSS.…”
Section: Discussionmentioning
confidence: 77%
“…She had bilateral functional ovarian cysts and a torsion of unilateral adnexa, and underwent surgical treatment. Terada et al [14] also reported a case of a large ovarian follicular cyst with torsion, whose serum estradiol level was significantly increased. Cohen et al [15] suggested that all pre-Nasu/Miyazaki/Kiyonaga/Kawasaki/ Miyakawa menopausal breast cancer patients being treated with tamoxifen should be under close gynecological and ultrasonographic surveillance.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of action of tamoxifen in stimulating the development of ovarian cysts has not yet been fully explored. It was suggested that the mechanism of action of tamoxifen in inducing ovarian cysts in premenopausal women could be by a direct action on the ovaries to stimulate excessive growth of ovarian follicles, resulting in elevated estradiol levels [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation